2020
DOI: 10.1111/jfpp.15077
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of optimized physiochemical parameters of dried potato flakes obtained by refractive and convective drying techniques

Abstract: The present study investigates the physicochemical quality of potato flakes obtained by convective tray drying (CD) and refraction‐based dying (RBD) techniques. Drying process was optimized using the Box–Behnken design of Response Surface Methodology to study the effect of drying temperature (CD: 50–70°C; RBD: 70–90°C), blanching time (3–5 min), and total soluble solids (8–12°Brix) on potato flakes characteristics. All polynomial regression response surface models obtained were significant (p < .05) with a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…This was due to increase in ‘L’ value of carrot, hence increasing overall colour change value when compared with fresh produce. The rise in water temperature also resulted in an increase in colour change, which may be ascribed to an increase in ‘a’ value than the ‘b’ value of black carrot powder 33 . The increase in ‘a’ value has been reported in various foods owing to chemical reaction that occurs between amino acids and reducing sugars while processing at higher temperatures which generate brown colour and subsequent occurrence of Milliard’s reaction 34 .…”
Section: Resultsmentioning
confidence: 99%
“…This was due to increase in ‘L’ value of carrot, hence increasing overall colour change value when compared with fresh produce. The rise in water temperature also resulted in an increase in colour change, which may be ascribed to an increase in ‘a’ value than the ‘b’ value of black carrot powder 33 . The increase in ‘a’ value has been reported in various foods owing to chemical reaction that occurs between amino acids and reducing sugars while processing at higher temperatures which generate brown colour and subsequent occurrence of Milliard’s reaction 34 .…”
Section: Resultsmentioning
confidence: 99%
“…Greater a *, b *, and BI values in TD samples compared to the FD sample could be described by brown color development during drying process. When the sample was subjected to dry under convective hot air drying, its compositions such as carbohydrates and protein were then exposed to heat resulting in the development of non‐enzymatic browning reactions (Maillard reaction, caramelization, and dextrinization) (Phahom et al, 2021; Shende & Datta, 2020; Tontul & Topuz, 2017; Zalpouri et al, 2021). From the results, it could be summarized that a * (redness), b * (yellowness), and BI values could be used to evaluate the development of brown color during drying process.…”
Section: Resultsmentioning
confidence: 99%
“…Various researchers have studied the effect of different hot air drying conditions on the quality attributes of food materials. The results demonstrated that higher drying temperature provided higher rehydration ratio (Phahom et al, 2021;Phungamngoen et al, 2016), porosity (Phungamngoen et al, 2016), browning index (Zalpouri et al, 2021) and total color difference (Luangmalawat et al, 2008) as well as less structural shrinkage (Phungamngoen et al, 2016), and hardness (Phungamngoen et al, 2016) compared to drying at lower temperature. In addition, the effect of convective hot air drying on rehydration properties of crab stick by-product has been studied by Phahom et al (2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that those flakes obtained by refraction-based drying had better nutritive value, color and acceptability. It recommended its application for the fortification of flour, baby foods, and extruded products [39]. Previously, a study in anthocyanin-rich red potato flakes showed that might improve the antioxidant system by enhancing hepatic SOD (superoxide dismutase) mRNA in mice [40].…”
Section: Red and Purple Flesh Potato-based Food And Natural Ingredients Responding To New Global Food Market Trendsmentioning
confidence: 99%